Práticas educativas de produção de textos escritos nos 4ºs e 5ºs anos - Giampaolo, Jessica (Universidade Federal de São Carlos, 2024)
The present research aims to analyze educational practices used by teachers in the development of the production of written texts in the teaching of the Portuguese Language, specifically in the 4th and 5th years of Elementary Education, with main purpose of contributing to reflection on how such practices can help in magnification of the use of the language in the post-literacy period. The research question is defined as follows: "What educational practices do teachers use to develop the written text production of students in the 4th and 5th grades of Elementary School in Portuguese Language classes?". Based on the concepts of Bardin (1977), a categorical and thematic analysis was conducted on the educational practices used by five teachers aiming at the development of written text production in a state public school in the municipality of São Carlos. The study continues based on reflection on the conception of language by Bakhtin (1997), Bagno (2012) and Travaglia (2009), on the definitions of text genre and mastery of language by Dolz, Noverraz e Schneuwly (2004), Marcushi (2008) and Bezerra (2017), in the concepts of Freire (1987), Zabala (1998), Possenti (2000) and Oliveira (2006) about educational practices, and in the reflections on textual productions, coherence and cohesion of written texts by Geraldi (1995, 2004), Atunes (2005), Reyes and Piccoli (2011) and Bueno, Mascia and Scaransi (2016). This research follows a qualitative approach involving semi-structured interviews with five teachers from the 4th and 5th years of Elementary Education about their educational practices in producing written texts. The results indicated that the teachers follow the “Currículo Paulista”, but criticize the materials for being outdated and inadequate, mentioning the need to complement and adapt the activities. It was also found that the teachers prefer to begin work on text production with retextualizations, aiming to create written retellings of model texts. They consider collective and paired productions more effective, as the students become more confident and active, while Individual texts tend to have more errors. The difficulties pointed by the teachers in autonomous writing indicated the need for improvement in the proposals. About the use of digital technologies as teaching resources, although they recognize their benefits, they mention that state schools are not always well equipped. The teachers reported successful practices, such as collective productions, complaint letters, mystery storybooks, and seminars, highlighting student interaction and motivation. The results and data analysis contributed to the reflection on how written texts helps to in magnification of the use of the language, leading the student to comprehend their reality, to develop mastery of language to navigate everyday life through it. The educational product of this study consisted of a guide with suggestions for educational practices to develop written text productions in the post-literacy phase, available in e-book format.
Educational practices for the production of written texts in the 4th and 5th years
Keywords: Produção de textos escritos; 4º ano; 5º ano; Práticas educativas; Ensino fundamental; Anos iniciais; CIENCIAS HUMANAS::EDUCACAO::ENSINO-APRENDIZAGEM